2020
DOI: 10.1590/1516-3180.2020.0221.r2.22072020
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary embolism in patients with COVID-19 and its treatment based on low-molecular-weight heparin

Abstract: In late 2019, a large number of pneumonia patients were diagnosed as having a disease of unknown cause in Wuhan, China. Following this outbreak of human symptoms and infections, a novel coronavirus was identified as the pathogen. In February 2020, the World Health Organization (WHO) named this novel coronavirus COVID-19. 1 In studies on patients, fever, coughing, myalgia or fatigue were identified as common symptoms, and production of sputum, headache, hemoptysis and diarrhea as less common symptoms. Dyspnea w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
(24 reference statements)
0
1
0
Order By: Relevance
“…The decrease of D-dimer serum after we gave LMWH were happen in all of the patients with value 0.8 (range 0.4-1.8) vs. 0.4 (range 0.2-1.0) (Table 2 and Figure 1). Studies showed that heparin affect patients with COVID-19 positively, but noted that uncertainties remained about the heparin dose that would be most effective, and about monitoring of complications (Hosseini & Bahramnezhad, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…The decrease of D-dimer serum after we gave LMWH were happen in all of the patients with value 0.8 (range 0.4-1.8) vs. 0.4 (range 0.2-1.0) (Table 2 and Figure 1). Studies showed that heparin affect patients with COVID-19 positively, but noted that uncertainties remained about the heparin dose that would be most effective, and about monitoring of complications (Hosseini & Bahramnezhad, 2020).…”
Section: Resultsmentioning
confidence: 99%